Evidence for the stability of the West Antarctic Ice Sheet divide for 1.4 million years - Andrew S. Hein (Nature Portfolio, 2016)
Predicting the West Antarctic Ice Sheet's response to future warming is hindered by a lack of historical evidence. Here, based on geomorphological evidence from and cosmogenic dating of Ellsworth Mountains' deposits, the authors show that at least a regional ice sheet survived Pleistocene interglacial cycles.